(untitled) (Hematology Meeting Reports, 2009)
T-cell acute lymphoblastic leukemia (T-ALL) and T-cell lymphoblastic lymphoma (T-LBL) are aggressive neoplasms derived from malignant transformation of lymphoblasts committed to T-cell lineage. Because of their morphological, immunophenotypic and clinical similarities, they have often been thought to represent a spectrum of a single disease, and the distinction between them had sometimes been arbitrary. Following the pediatric experience, the main current therapies for both T-ALL and T-LBL in adults are based on intensive induction chemotherapy, including central nervous system prophylaxis, and a prolonged maintenance phase. Despite complete remission rates up to 80-90%, similar to those obtained in children, the prognosis in adults is less favourable, mainly because of high rates of relapse. A convincing prognostic model to determine which patients have to be offered more intensive consolidation, such as stem cell transplantation, is lacking. However, recent biological studies provided the evidence for a number of differences in the molecular and genetic profiles between T-ALL with different outcome and between T-ALL versus T-LBL. The precise definition of the aberrant molecular pathways relevant for the pathogenesis of neoplastic cells as well as the possibility to accurately evaluate the treatment response by minimal residual disease studies will probably be worthwhile in defining more precise prognostic models and in developing new target therapies.